Brain metabolism in patients with freezing of gait after hypoxic-ischemic brain injury: A pilot study. Issue 45 (November 2017) - Yoon, Seo Yeon; Lee, Sang Chul; Kim, Na Young; An, Young-Sil; Kim, Yong Wook
Abstract : Abstract: Movement disorders are 1 of the long-term neurological complications that can occur after hypoxic-ischemic brain injury (HIBI). However, freezing of gait (FOG) after HIBI is rare. The aim of this study was to examine the brain metabolism of patients with FOG after HIBI using F-18 fluoro-2-deoxy-D-glucose positron emission tomography (F-18 FDG PET). We consecutively enrolled 11 patients with FOG after HIBI. The patients' overall brain metabolism was measured by F-18 FDG PET, and we compared their regional brain metabolic activity with that from 15 healthy controls using a voxel-by-voxel-based statistical mapping analysis. Additionally, we correlated each patient's FOG severity with the brain metabolism using a covariance analysis. Patients with FOG had significantly decreased brain glucose metabolism in the midbrain, bilateral thalamus, bilateral cingulate gyri, right supramarginal gyrus, right angular gyrus, right paracentral lobule, and left precentral gyrus ( P FDR-corrected < .01, k = 50). No significant increases in brain metabolism were noted in patients with FOG. The covariance analysis identified significant correlations between the FOG severity and the brain metabolism in the right lingual gyrus, left fusiform gyrus, and bilateral cerebellar crus I ( P uncorrected < 0.001, k = 50). Our data suggest that brain regions in the gait-related neural network, including the cerebral cortex, subcortical structures, brainstem, and cerebellum, may significantly contribute to the development of FOG in HIBI. Moreover, the FOG severity may be associated with the visual cortex and cerebellar regions.